Low geriatric nutritional risk index is associated with osteosarcopenia in older patients with type 2 diabetes mellitus - Xiaoye Duan; Jagadish K. Chhetri; Lina Sun; Zhijing Mu; Junling Fu; Shuangling Xiu (BMC Musculoskeletal Disorders)
Abstract Background The association between the geriatric nutritional risk index (GNRI) and osteosarcopenia in older adults with type 2 diabetes mellitus (T2DM) is not clear. Methods A total of 573 individuals with T2DM were included in this cross-sectional study. Osteosarcopenia was defined as the presence of both osteoporosis and sarcopenia. Appendicular skeletal muscle mass and bone mineral density (BMD) was measured by dual energy X-ray absorptiometry to diagnose sarcopenia and osteoporosis. Multivariate analyses were used to assess the association between Geriatric Nutritional Risk Index (GNRI) and osteosarcopenia. Results The patients were divided into four groups: robust (n = 367), osteoporosis alone (n = 154), sarcopenia alone (n = 29), and osteosarcopenia (n = 23). The GNRI was the lowest in osteosarcopenia group and was positively correlated with skeletal muscle index (SMI) (r = 0.122, p = 0.004), grip strength (r = 0.154, p < 0.001), gait speed (r = 0.123, p = 0.004), and BMD of lumbar spine 2–4, femoral neck, and total hip (r = 0.137, p = 0.002; r = 0.096, p = 0.028; r = 0.086, p = 0.049, respectively). In the logistic regression model low GNRI was significantly associated with an increased risk of osteosarcopenia (adjusted OR, 4.164; 95% CI, 1.283–13.514, p = 0.018). Age provided a discriminatory effect of osteosarcopenia with an area under the curve (AUC) of 0.764. When GNRI values were added to the model, the value of the ROC curve was further improved, with an AUC of 0.842. Conclusion Low GNRI was associated with an increased risk of osteosarcopenia in older adults with T2DM. Comprehensive clinical evaluation of nutritional status by a simple tool such as GNRI might be helpful for early identification of those at high risk for osteosarcopenia in older diabetic individuals.